School Refusal Behavior Profiles, Optimism/Pessimism, and Personality Traits in Spanish Children - Miriam Martín; Carolina Gonzálvez; María Vicent; Ricardo Sanmartín; Aitana Fernández-Sogorb; José M. García-Fernández (MDPI AG, 2021)
The relationship between school refusal behavior (SRB) profiles and personality traits has received little attention from investigators. Identifying the profiles of students with school attendance problems may improve the understanding of the characteristics defining these students. The aim of this study was to identify different SRB profiles and analyze the relationship between these profiles, and optimism/pessimism and personality traits. The School Refusal Assessment Scale-Revised, the Youth Life Orientation Test, and the Big Five Questionnaire were administrated to 739 Spanish students aged 8-11 (Mage = 9.92; SD = 1.12). Pearson's correlation coefficients revealed a significant association between personality dimensions and SRB. Three distinct profiles were identified: (1) SRB by negative reinforcement (high scores on avoiding school-related stimuli provoking negative affectivity), (2) SRB by positive reinforcement (high scores on pursuing positive tangible reinforcement outside of school), and (3) Low SRB. The SRB profile by positive reinforcement scored higher on Extraversion, Agreeableness, Conscientiousness, Openness, and Optimism, whereas the SRB profile by negative reinforcement scored higher on Neuroticism and Pessimism. More statically significant differences were found between the negative and positive reinforcement profiles. The role of negative personality traits and pessimism as risk factors for students who are truant or refuse to attend school are discussed.